Antioxidant Activity and Chemical Alterations of Honeybee Brood Bio-Peptides Interacting with Honey Under Moist-Dried Thermal Aging - Supakit Chaipoot; Pairote Wiriyacharee; Pattavara Pathomrungsiyounggul; Gochakorn Kanthakat; Chalermkwan Somjai; Kongsak Boonyapranai; Sirasit Srinuanpan; Worachai Wongwatcharayothin; Rewat Phongphisutthinant (Antioxidants)
Edible insect honeybee brood and natural honey are rich in proteins and saccharides, with inherent bioactive properties such as antioxidant activity. To enhance their antioxidative potential under simple thermal conditions, this research employed spontaneous aging via a moist-dried heating process, primarily driven by the Maillard reaction. Honeybee brood bio-peptides (HBb-BPs), produced through Rhizopus oligosporus fermentation, were mixed with honey in varying ratios of 70:30, 50:50, and 30:70 (%w/w). The mixtures underwent interaction under controlled conditions (60 °C for 20 days at ~75% relative humidity). A comparative analysis was performed on the mixtures before and after the thermal interaction, focusing on chemical characterization and antioxidant activity (ABTS, DPPH, and FRAP assays). Results revealed that the post-process mixtures exhibited significantly enhanced antioxidant activity, with higher honey concentrations correlating to greater antioxidative effects. Furthermore, allulose and mannose were detected after processing, while levels of fructose, glucose, and free amino acids decreased. These changes likely indicate the formation of complex compounds, molecular rearrangements, and the production of phenolic compounds that contributed to the increased antioxidative capacity. This study highlights the pivotal role of the Maillard reaction in augmenting antioxidant activity, elucidates changes in sugar–amino acid interactions, and validates the effectiveness of the moist-dried heating process. These findings provide valuable insights for potential future applications of this simple and scalable method.